2009
DOI: 10.1002/path.2605
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐D deficiency in mice does not affect embryonic or postnatal lymphangiogenesis but reduces lymphatic metastasis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 58 publications
3
33
3
Order By: Relevance
“…VEGFC is a critical regulator of this process (6,7), but the VEGFC homolog VEGFD appears to play no required role in lymphatic development and has been linked instead to postnatal lymphangiogenesis (12). VEGFC and VEGFD contain N-and C-terminal extensions that are not found in VEGFA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGFC is a critical regulator of this process (6,7), but the VEGFC homolog VEGFD appears to play no required role in lymphatic development and has been linked instead to postnatal lymphangiogenesis (12). VEGFC and VEGFD contain N-and C-terminal extensions that are not found in VEGFA.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that VEGFD proteolysis takes place independently of ADAMTS3 and CCBE1, both ex vivo and in vivo, demonstrates a remarkable difference in the regulation of these 2 lymphangiogenic factors that provides new insight into their distinct in vivo roles. Gain-of-function studies revealed that VEGFC and VEGFD have equally powerful lymphangiogenic effects in vivo (15,38), but genetic loss-of-function studies have only demonstrated a critical role for VEGFC during lymphatic development (6,12). If the primary role of ADAMTS3-CCBE1 processing is to lay down a roadmap of activated VEGFR3 ligand that LECs follow to create the primary lymphatic network, then this can only be accomplished by VEGFC.…”
Section: Activation Of Vegfr3 By Vegfc Requires N-and C-terminal Protmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial remodeling or regrowth was assessed in the lung during pulmonary hypertension 35 and in the skin during healing of a full-thickness skin wound, 36 as detailed in the supplemental material.…”
Section: Phenotypic Analysismentioning
confidence: 99%
“…Studies in humans have determined a direct correlation between VEGF-C/VEGF-D and lymphatic invasion, lymph node, and distant organ metastasis (6,9,11). Neutralization of VEGF-D with specific antibody or genetic deficiency of VEGF-D appears to suppress tumor metastasis in mice (12,13). VEGF-C has been shown to induce intercellular gaps that facilitate entry of tumor cells into the lumen of the vessels (14).…”
Section: Introductionmentioning
confidence: 99%